2017
DOI: 10.5301/uj.5000246
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre Experience with ZSI 375 Artificial Urinary Sphincter for the Treatment of Stress Urinary Incontinence in Men

Abstract: Objectives The aim of this study was to evaluate the safety and efficacy of the artificial urinary sphincter ZSI 375 device in male patients with stress urinary incontinence (SUI) at 10 centres. Methods This was a retrospective, nonrandomised, multicentre study. From January 2012 to December 2014, and follow-up to February 2016, men with SUI were treated with the ZSI 375 device. The primary outcome was continence. The secondary outcome was complications rate. Results A total of 147 patients with moderate-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
3
11
0
2
Order By: Relevance
“…Farag et al 15 found a shorter time to revision in their salvage cohort after implantation of a male sling. It is not clear whether prefilled sphincter models like the ZSI 375 (Zephyr Surgical Implants, Switzerland) may be an alternative for low‐volume centers; only data from a few centers with high levels of expertise have been published thus far 16 . An emerging innovation in artificial sphincter systems is adjustability.…”
Section: Discussionmentioning
confidence: 99%
“…Farag et al 15 found a shorter time to revision in their salvage cohort after implantation of a male sling. It is not clear whether prefilled sphincter models like the ZSI 375 (Zephyr Surgical Implants, Switzerland) may be an alternative for low‐volume centers; only data from a few centers with high levels of expertise have been published thus far 16 . An emerging innovation in artificial sphincter systems is adjustability.…”
Section: Discussionmentioning
confidence: 99%
“…All surgeons reported the implantation of BR - SL - AR 908 being straightforward, fast, feasible and reproducible, with also a short learning curve to achieve mastery (personal findings). Unlike the facility offered by our device, the gold standard sphincter (AM800) is still provided in several boxes and separated components to assemble during the procedure with a constraining preparation (12). In addition, none of patients submitted to our implant presented trans - operative or postoperative complications related to the surgical procedure, using Clavien - Dindo score (13).…”
Section: Discussionmentioning
confidence: 99%
“…Eight weeks later the AUS was activated in an outpatient setting. A detailed description of the ZSI 375 artificial sphincter implantation procedure was presented in earlier publications [ 5 , 7 , 8 ].…”
Section: Methodsmentioning
confidence: 99%